‘‘Building hope for the future’’: A program to foster strengths in middle-school students - Marques, Susana C. (2012)
The authors investigated the effectiveness of a 5-week hope-based intervention designed to enhance hope, life satisfaction, self-worth, mental health and academic achievement in middle school students. The study includes a sample of 31 students from a community school, a matched comparison group of 31 students, and 2 secondary groups— guardians and teachers of the students’ intervention group. Students completed a questionnaire packet that included demographic information, the Portuguese versions of the Children’s Hope Scale, Students’ Life Satisfaction Scale, Mental Health and Self-Worth Scales. Academic achievement was obtained from school records. At baseline, groups are statistically similar on the variables of interest. At post-test the intervention group had enhanced hope, life satisfaction and self-worth. In the intervention group, benefits in hope, life satisfaction and self-worth were maintained at the 18-month follow up. Results suggest that a brief hope intervention can increase psychological strengths, and participants continue to benefit up to 1-year and 6-months later.